Answer: negative 1 minus another negitive 1 give you zero/X
Step-by-step explanation:
Answer:116
Step-by-step explanation: 5x-2=4x+10
x=12
double the angle to get the arc
Answer:
1.)
Step-by-step explanation:
When driving downwards, that is negative because you are subtracting. Then, when driving upwards, you are adding.
The function
represents a reflection of
across the y-axis ⇒ 3rd answer
Step-by-step explanation:
Let us revise the reflection across the axes
- If the function f(x) reflected across the x-axis, then its image is g(x) = - f(x)
- If the function f(x) reflected across the y-axis, then its image is g(x) = f(-x)
∵ ![f(x)=6(\frac{1}{3})^{x}](https://tex.z-dn.net/?f=f%28x%29%3D6%28%5Cfrac%7B1%7D%7B3%7D%29%5E%7Bx%7D)
∵ g(x) is the image of f(x) after reflection across the y-axis
- From the rule above reflection across the y-axis changes the sign of x
∴ ![g(x)=6(\frac{1}{3})^{-x}](https://tex.z-dn.net/?f=g%28x%29%3D6%28%5Cfrac%7B1%7D%7B3%7D%29%5E%7B-x%7D)
∵ ![(a)^{-n}=(\frac{1}{a})^{n}](https://tex.z-dn.net/?f=%28a%29%5E%7B-n%7D%3D%28%5Cfrac%7B1%7D%7Ba%7D%29%5E%7Bn%7D)
∵ ![(\frac{1}{a})^{-n}=(a)^{n}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7Ba%7D%29%5E%7B-n%7D%3D%28a%29%5E%7Bn%7D)
∴ ![(\frac{1}{3})^{-x}=(3)^{x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%5E%7B-x%7D%3D%283%29%5E%7Bx%7D)
∴ ![g(x)=6(3)^{x}](https://tex.z-dn.net/?f=g%28x%29%3D6%283%29%5E%7Bx%7D)
The function
represents a reflection of
across the y-axis
Learn more:
You can learn more about reflection in brainly.com/question/5017530
#LearnwithBrainly